2017
DOI: 10.1007/s11144-017-1329-1
|View full text |Cite
|
Sign up to set email alerts
|

Front dynamics of pH oscillators with initially separated reactants

Abstract: The spatiotemporal dynamics of the Landolt-type pH oscillators are studied both numerically and experimentally with initially separated reagents in space. This configuration results in an A + B → oscillator front type system with localized patterns. The generic Rábai model of the pH-oscillators predicts the formation of an asymmetric acidic domain at the interface of the two zones loaded by different sets of chemicals. This asymmetry is rather caused by the initial conditions than the difference in the diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The addition of bromide ions improves the visibility of the pattern by increasing its wavelength, which is also a desired feature in this context. It can be used not only with the CDIMA but with other nonlinear chemical reactions, for example, the BZ reaction 18 and Landolt-type pH oscillators 25 to study RD phenomena at special initial and boundary conditions. As an exclusive feature, it is easy to change the direction of observation in successive experiments because the switch between SbS and TaB geometries can be achieved without a hitch.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of bromide ions improves the visibility of the pattern by increasing its wavelength, which is also a desired feature in this context. It can be used not only with the CDIMA but with other nonlinear chemical reactions, for example, the BZ reaction 18 and Landolt-type pH oscillators 25 to study RD phenomena at special initial and boundary conditions. As an exclusive feature, it is easy to change the direction of observation in successive experiments because the switch between SbS and TaB geometries can be achieved without a hitch.…”
Section: Discussionmentioning
confidence: 99%
“…18 To search for experimental evidence of our predicted oscillating viscous ngering dynamics, the recent viscous ngering obtained using a clock reaction 26 with pH-changing properties 25 is a good starting point. The fact that front dynamics in A + B → oscillator con gurations also start to be experimentally available in pH oscillators 23 enriches the possibility of trying to tune ngering using Chaos ARTICLE scitation.org/journal/cha pH-sensitive polymers. 10,11 It would be very nice to be able to couple viscous e ects with the canonical oscillating Belousov-Zhabotinky reaction around an A + B → oscillator con guration.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Localized oscillations 19 or stationary Turing patterns 20,21 can be obtained in autocatalytic reactions around A + B → oscillator fronts when putting in contact two zones containing separate reactants A and B of an oscillatory reaction. 17,18,22,23 From the theoretical point of view, it has been shown that localized oscillations and Turing structures can interact with buoyancy-driven ows when the reactants A and B of the oscillatory Brusselator model are initially separated, meet by di usion, and produce the intermediate X and Y species locally, which changes the density. 18 Experimentally, interplay between the oscillating Belousov-Zhabotinsky (BZ) reaction and buoyancy-driven motions has been analyzed when two subsets of the reactants are put in contact along a horizontal line in the gravity eld.…”
Section: Introductionmentioning
confidence: 99%
“…During the last three years, we have started to explore systematically the RD dynamics of H + -autocatalytic reactions in reactors with separated sources of reactants [25][26][27]. In our experiments, the BS-based reactions-above all the BSF system-were preferred to use.…”
Section: Reaction-diffusion Patterns In Gel Reactors With Separated Sources Of Reactantsmentioning
confidence: 99%
“…A and B indicate different subsets of reactants. For details see References [25][26][27] (Fig. 6a and c).…”
Section: Reaction-diffusion Patterns In Gel Reactors With Separated Sources Of Reactantsmentioning
confidence: 99%